Real time game field limits recognition for robot self-localization using collinearity in middle-size roboCup soccer - Ribeiro, A. Fernando (2003)
Enabling a mobile robot to achieve its self-localization in real-time with vision only, demands for new approaches and new computer algorithms. An approach for giving game field self-localization to a Middle Size RoboCup Soccer robot can be based in two steps: finding the game field lines and evaluating the obtained coordinates calculating the robot coordinates. This paper describes a method to achieve the first step. This approach is based on an algorithm that combines three major features: edge detection, selection and collinearity search. The final target is to retrieve the line segments (defined by its two limits coordinates), which identify the game field boundary lines. These line coordinates will be used on the next step that is the process to calculate the robot position in the game field. Since this first step is to find lines in real time, it is an alternative method to the Hough Transform Method.